An Ecological Systems Perspective on Individual Differences in Children's Performance on Measures of Executive Function - Holochwost, Steven J.; Winebrake, Deaven; Brown, Eleanor D.; Happaney, Keith R.; Wagner, Nicholas J.; Mills-Koonce, W. Roger (Journal of cognition and development, 2023)
The predictive validity of performance on cognitive-behavioral measures of executive function (EF) suggests that these measures index children's underlying capacity for self-regulation. In this paper, we apply ecological systems theory to critically evaluate this assertion. We argue that as typically administered, standard measures of EF do not index children's underlying, trait-like capacity for EF, but rather assess their state-like EF performance at a given point in time and in a particular (and often quite peculiar) context. This underscores the importance of disentangling intra-individual (i.e., state-like) and inter-individual (trait-like) differences in performance on these measures and understanding how factors at various levels of organization may contribute to both. To this end, we offer an approach that combines the collection of repeated measures of EF with a multilevel modeling framework, and conclude by discussing the application of this approach to the study of educational interventions designed to foster children's EF.